Unusual Presentation of Duodenal Ulcer Presenting with Duodenal Intussusception - Lingala, Shilpa (ACG Case Rep J, 2018)
We present a unique case of duodeno-duodenal intussusception from a duodenal bulb ulcer. A 38-year-old man presented with nausea, vomiting, and abdominal pain. Computed tomography showed duodenal intussusception. Esophagogastroduodenoscopy (EGD) showed a linear gastric ulcer and a duodenal bulb ulcer with an overlying blood clot. Helicobacter pylori status was positive. Intussusception resolved spontaneously without intervention. He completed treatment for H. pylori infection, and repeat EGD showed ulcer healing. Duodenal intussusception is rarely reported; intussusception from an edematous duodenal ulcer with an overlying blood clot mimicking a mass lesion acting as lead point has never been reported to our knowledge.